دور تطوير المنتج الفلسطيني في اكتساب ميزة التنافسية لمواجهة المنتج الإسرائيلي دراسة حالة: شركة سنقرط للمنتجات الغذائية - obaid, shaher; rasslen, mohammad (Finance and Business Economies Review, 2017)
This study aimed at identifying the role of Palestinian product development to gain competitive advantage to face the Israeli product at the Palestinian industrial companies in West Bank, followed the descriptive approach by applying a questionnaire on a total sample size of (150) employees at (Sinokrot) company, after data collection and analysis results showed that the development of Palestinian product contributes to gain the competitive advantage that makes the national item able to compete with Israeli product, the researchers recommended the necessity for the Palestinian Authority to encourage local production to compete with Israeli products, by giving national companies advantages and facilities to enable them developing their products